Environmental chemicals and public sociology: engaged scholarship on highly fluorinated compounds. Issue 4 (2nd October 2019) - Cordner, Alissa; Richter, Lauren; Brown, Phil
ABSTRACT: We report here on a multifaceted body of research on per- and polyfluoroalkyl substances (PFAS), chemicals that have become a well-known group of 'emerging contaminants' in recent years. Our PFAS Project team of over 10 researchers – faculty, postdocs, graduate students, and undergraduates – has been working since 2015 to study the extent and health effects of PFAS contamination through a broad model of engaged public sociology. Our model of research combines organic public sociology with elements of community-based participatory research, a related but distinct research form most widely used in the environmental health sciences. Based on long-term, place-based relationships, our engaged public sociology has led to numerous academic, regulatory, and social movement effects. We argue that this form of engaged, intervention-oriented public sociology is appropriate and beneficial for research in many areas of environmental sociology given the social and ecological stakes in the current moment. Engaged public sociology involves collaborative, reflexive research with broadly-conceived communities or publics. It facilitates the creation of previously undone science by addressing research topics of interest to community members, and allows researchers to directly contribute to environmental and social justice movements by acting as reflexive, observant participants.